KEBANGKITAN HAK-HAK SIPIL PENGHAYAT KEPERCAYAAN PARMALIM PASCA PASAL 61 AYAT (1) PUTUSAN MAHKAMAH KONSTITUSI NOMOR 97/PUU-XIV/2016 DI KOTA MEDAN - Gomgom T. P Siregar; Rudolf Silaban; Peri Gustiranda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at finding the truth and the inclusion of words of believers in the electronic identity card, especially followers of Parmalim in the city of Medan even though the religious column on their electronic KTP is blank or a sign (-). The research method used in this study is normative juridical, which uses a library study on Population Administration Law to the 2016 Constitutional Court Number and Constitutional Court Decision Number 97 / PUU-XVI / 2016 in Medan City. The research result is that the civil rights of the trustees, namely the right to social security, have easy access to population documents such as electronic ID cards, family cards, marriage certificates and birth certificates for Parmalim in the city of Medan. May have access to work, can access rights to social security, can access population documents such as electronic ID cards, family cards, marriage certificates and birth certificates. Likewise, the applicant's children may apply for a job even though the religious column on the electronic KTP is marked with a strip or (-).